1997
DOI: 10.1074/jbc.272.37.23086
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Ubiquitin-dependent Pathway in Response to Oxidative Stress

Abstract: Relations between the ubiquitin pathway and cellular stress have been noted, but data regarding responses of the ubiquitin pathway to oxidative stress are scanty. This paper documents the response of this pathway to oxidative stress in lens cells. A brief exposure of lens epithelial cells to physiologically relevant levels of H 2 O 2 induces a transient increase in activity of the ubiquitindependent pathway. Ubiquitin conjugation activity was maximal and increased 3.5-9.2-fold over the activity noted in untrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
135
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 215 publications
(145 citation statements)
references
References 73 publications
8
135
2
Order By: Relevance
“…Recently, we demonstrated that the ubiquitin pathway is also regulated by cellular redox status (JahngenHodge et al, 1997;Obin et al, 1999;Shang et al, 1997b) and that it is the major cellular pathway for removal of oxidized proteins Shang et al, 1997a). Taken together with data which suggest elevated oxidant sensitivity in A-T cells, it would appear that sequelae due to the absence of a functional ATM protein might involve the ubiquitin pathway as well.…”
Section: Introductionmentioning
confidence: 81%
See 4 more Smart Citations
“…Recently, we demonstrated that the ubiquitin pathway is also regulated by cellular redox status (JahngenHodge et al, 1997;Obin et al, 1999;Shang et al, 1997b) and that it is the major cellular pathway for removal of oxidized proteins Shang et al, 1997a). Taken together with data which suggest elevated oxidant sensitivity in A-T cells, it would appear that sequelae due to the absence of a functional ATM protein might involve the ubiquitin pathway as well.…”
Section: Introductionmentioning
confidence: 81%
“…We used H 2 O 2 in further experiments because (1) this would allow us to compare these results with prior information regarding the e ects of H 2 O 2 on ubiquitination capabilities in other types of cells (from both fast and slowly metabolizing tissues), (2) H 2 O 2 is encountered in many physiological conditions, and (3) because there was little data which related NCS treatment to alterations in redox status (Adamo et al, 1999;Jahngen-Hodge et al, 1997;Obin et al, 1998;Ramanathan et al, 1999;Shang et al, 1997b). The experiments were done at three cell densities: 0.3610 6 , 0.6610 6 and 1.0610 6 cells/mL in order to assure that cell density alone did not cause changes in ubiquitin conjugates.…”
Section: Ubiquitin Conjugates Change Upon Treatment With Ncsmentioning
confidence: 99%
See 3 more Smart Citations